Penentu Utama Keputusan Pembelian: Evaluasi Kualitas Produk dan Daya Tarik Visual Kemasan Minuman - Anna Kridaningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In an increasingly competitive business, companies must be able to understand what factors will influence the decision to buy. This study intends to analyze the role of packaging quality and design on the decision to buy Fatigon Hydro isotonic drinks among 100 respondents in Surabaya City. The study involved purposive sampling method to select respondents who have sufficient experience and understanding of Fatigon Hydro isotonic drink products. The study utilized quantitative methods. Statistical analysis, including regression, was used to evaluate the influence between product quality and design on packaging with the decision to purchase. The results showed that the design on the packaging contributed positively to the decision-making. In addition, consumers tend to give high value to products that are considered good quality or in accordance with consumer desires.